Technology for test-systems for diagnosis of modified proteins (proteopathy) underlying social diseases (Report 1) - Ya. M. Stanishevskiy; I. A. Gritskova; N. S. Kuzmina (Тонкие химические технологии)
A new experimental technique for obtaining diagnostic test systems is introduced based on conjugates "polymer microsphere–bioligand" for rapid diagnosis of autoantibodies to the modified protein on example of thyroglobulin, which consists of preliminary blocking of aldehyde groups of polymer microspheres by glycine amine groups, and then of the covalent interaction between carboxyl group of glycine and the amino groups of thyroglobulin. This way of creating test systems has enhanced the sensitivity of the reaction of latex agglutination (RLA) by extending the boundaries of titer.